An Analysis of Second Semester Students Afternoon Session Class of Stikom Tunas Bangsa by Critical Thinking Skill - Susiani; Rizki, Fitri; Sormin, Rizky Khairunnisa (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
Critical thinking is the ability to analyze information objectively and logically, forming reasoned judgements. It is one of very necessary skills to traine to second semester students of Stikom Tunas Bangsa in the afternoon session class. Research-based learning (RBL) presents as an alternative learning model that can develop the critical thinking skills. This study aims at describing the effect of the implementation to the research-based learning (RBL) to develop fourth semester students’ critical thinking skills. Qualitative approach was used in the classroon research. The participants in this study consisted of 106 students. Data were collected using observation and test. The results of the research indicate that the implementation research-based learning (RBL) can develop critical thinking skills. It is proved by the fact that the students were able to show their interpretation, analysis, evaluation, inference and explanation abilities. Meanwhile, aspect of self-regulation ability has not yet been able to be found. This research were used to make more sure previous research that implementation of the RBL can improve the quality learning process and make positive changes for the students in the intellectual and emotional. This research provides a different learning experience which can develop critical thinking skill.